Integrated displacement ventilation system precast wall - Arman, Muhammad Afiq (2022)
Sustainability can be defined as the capacity to support or maintain a process constantly across time. Sustainability aims to stop the depletion of natural or physical resources in business and policy contexts to be accessible in the long run. The topic of sustainability has become popular in the recent decade since environmental issues have become more apparent throughout the day—for example, climate change, global warming, and natural disasters. In the construction industry, modularity in construction building structures, such as the Industrialised Building System (IBS) method, is being pushed around the world as one of the methods to support the sustainability effort. Other than that, the supporting mechanicals to run the building is also being improved over time in terms of occupant comfort and energy usage. Therefore, this study focuses on building ventilation. Various innovative approaches to ventilate buildings, issues and problems with building ventilation are reviewed before the proposal of innovation. Therefore, the proposed innovation is the Integrated Displacement Ventilation System Precast Wall Panel. The proposed innovation promotes sustainability through several elements. The first element is the construction method which uses precast wall panels. The second element is using a highly efficient fan for the ventilation to best utilise the energy. And lastly, the encouragement of using natural air for sustainable living. The proposed innovation is described in detail regarding its assembly, performance, and marketability potentials.